Pengaruh pH dan Konsentrasi Terhadap Penyerapan Zat Warna Rhodamin B Menggunakan Karbon Aktif Kulit Pisang Kepok (Musa balbisiana Colla) - Muhamad Daviya Nur Fauzi; Edi Nasra; Ali Amran; Miftahul Khair (Jurnal Periodic Jurusan Kimia UNP, 2021)
Rhodamine B is a textile dye which can cause environmental pollution. Rhodamin B dyes found in waters can cause damage to ecosystems both animals and plants, so a method is needed to overcome the impact of pollution by Rhodamin B waste. One of the most efficient methods is the adsorption method using activated carbon from Kepok banana peels (Musa balbisiana Colla ). The purpose of this study was to determine the optimum conditions for absorption and optimum absorption capacity of Rhodamine B by batch method with variations in pH, concentration, particle size, stirring time and stirring speed. The results showed the absorption capacity at optimum conditions for the absorption of Rhodamine B at pH 4 and concentration of 150 mg / L.